Patterns of Symbolic Interaction Communication in the Online Ojek Community: Qualitative Descriptive Study - Ani Wahyu Rachmawati; Alifa Wulandari (International Journal of Education, Information Technology, and Others, 2023)
The emergence of Gojek, one of the start-ups that has been welcomed by the public, has created a new profession, namely Online Ojek (OJOL). The Ojek Online drivers then form small groups and communities in their respective areas with various goals. This study aims to conduct an exploratory study in identifying patterns of group communication carried out by the Online Ojek Community in the Bandung area, West Java. This study uses a descriptive qualitative method involving informants from Gojek Balantrax drivers using purposive sampling. The results of this study obtained a description of communication patterns in the Online Ojek group which involved symbolic interactions between individuals in the group. Intragroup communication patterns involve verbal and non-verbal communication, intrapersonal communication between individuals and cues. From this study it can be concluded that the pattern of group communication in the online motorcycle taxi community is unique by using terms that only members of the community understand